2011
DOI: 10.1007/s00705-011-1133-6
|View full text |Cite
|
Sign up to set email alerts
|

Encephalomyocarditis virus may use different pathways to initiate infection of primary human cardiomyocytes

Abstract: Encephalomyocarditis virus (EMCV) can infect a wide range of vertebrate species including swine and non-human primates, but few data are available for humans. We therefore wanted to gain further insight into the mechanisms involved in EMCV infection of human cells. For this purpose, we analyzed the permissiveness of primary human cardiomyocytes towards two strains of EMCV; a pig myocardial strain (B279/95) and a rat strain (1086C). In this study, we show that both strains productively infect primary human card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…Our data support that ADAM9 is a crucial protein for EMCV infection; specifically, ADAM9 knockout cells from two mammalian species are not infected by two different EMCV strains, reconstitution of ADAM9 permits EMCV infection, and virus replication is unaffected by ADAM9 deficiency when viral RNA is transfected directly into the cytosol. EMCV may directly bind to ADAM9, but we and others (57) have observed polysaccharide-related binding that may facilitate productive infection. Also, as a disintegrin, ADAM9 is known to affect expression of other cell surface proteins (27, 38); thus, expression of ADAM9 could lead to uncovering of another protein that is the actual binding “receptor” protein.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Our data support that ADAM9 is a crucial protein for EMCV infection; specifically, ADAM9 knockout cells from two mammalian species are not infected by two different EMCV strains, reconstitution of ADAM9 permits EMCV infection, and virus replication is unaffected by ADAM9 deficiency when viral RNA is transfected directly into the cytosol. EMCV may directly bind to ADAM9, but we and others (57) have observed polysaccharide-related binding that may facilitate productive infection. Also, as a disintegrin, ADAM9 is known to affect expression of other cell surface proteins (27, 38); thus, expression of ADAM9 could lead to uncovering of another protein that is the actual binding “receptor” protein.…”
Section: Discussionmentioning
confidence: 67%
“…Previous EMCV studies suggest that different strains of EMCV may bind to different receptors and that some EMCV strains may use multiple pathways (56, 57). In addition, EMCV strains with different tissue tropism have been identified (1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The viruses, which were cultured in baby hamster kidney-21 (BHK-21) cells, produced two groups of variants. Group I with Lys231 in VP1 that becomes Sia-dependent can bind to and infect primary human cardiomyocytes more efficiently than can group II with Arg231 in VP1, which is not a Sia-dependent group [92]. In addition, the rat strain 1086C appeared to acquire the ability to replicate effectively in buffalo rat liver (BRL) cells as a result of 3 amino acid mutations, Lys49Glu, Leu142Phe, and Ile180Ala, in VP1 that provided the ability to bind to the sialylated BRL cell 512 Nongluk Sriwilaijaroen and Yasuo Suzuki surface after 29 passages [87].…”
Section: Picornaviridaementioning
confidence: 96%
“…The crystal structures of the viral capsid proteins, VP1, VP2, VP3, and VP4, in complex with a sialyl ligand have shown that a Sia-binding pocket is in VP1 of ERAV [83], in a pit between VP1 and VP3 of EV-D68 [89], in VP1 of CVA24v [90], and mainly in the VP2 puff B of low-neurovirulent TMEV [88,91]. Analysis of EMCV mutants/ variants has indicated that amino acids in VP1 are responsible for interactions with Sia on the host cell surface [87,92]. Typically, binding of the viral capsid proteins of picornaviruses to receptors triggers endocytosis.…”
Section: Picornaviridaementioning
confidence: 99%